QUANTITATIVE ANALYSIS OF THE BEHAVIOR OF NATIONAL MEXICAN REAL ESTATE PRICES - Demmler, Michael; Gómez Hernández, Denise (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2020)
OBJECTIVE: To explain Mexican home prices using fundamental, macroeconomic variables in order to identify possible financial bubble tendencies within the Mexican national housing market during the period 2005 to 2018.MATERIAL AND METHOD: The present study analyzes quarterly data of Mexican real estate market prices and various fundamental, macroeconomic variables during the period 2005 to 2018. The quantitative research approach of the study is based on descriptive statistics and regression analyses.RESULTS: The main results of the study are as follows: First, a simple comparison between market prices and fundamental values shows some kind of (preliminary) evidence of bubble tendencies on the Mexican national real estate market. Secondly, a more sophisticated regression analysis concludes that especially the fundamental variables outstanding mortgage volume and unemployment rate can explain real estate market price movements almost perfectly.CONCLUSIONS: The hypothesis of a financial bubble within the national Mexican real estate market is then rejected, in the considered period 2005 to 2018.